Nilai Pendidikan Karakter dalam Londe Tomatua pada Buku Londe-londena Toraya - Elisabet Mangera; Haris Supratno (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to describe the value of education in Londe Tomatua in J.B.Lebang's book Londe-londena Toraya. The benefits of the results of this study are (1) as teaching material in Torajan literature courses (2) as a reference for research on other aspects of oral literature research, (3) providing benefits to readers in relation to Educational Values ​​in Londe Tomatua in the Londe Book -Londena Toraya by JB Lebang. This research is a qualitative type, namely a continuous research process so that the data collection, data processing, and data analysis stages are carried out simultaneously during the research process. The data obtained were analyzed using a procedure that produced descriptive data, namely the description of Educational Value in Londe Tomatua in J.B.Lebang's Londe-Londena Toraya Book. To collect data, the researcher used (1) reading technique, namely the researcher directly reading the object of research in the book that had been prepared by the researcher, (2) the note-taking technique, namely in this technique, data that met the requirements were recorded in the book provided by the researcher. . This means that the data about Londe Tomatua contained in the Londe-Londena Toraya Book by Pdt.J.B. Lebang, the researcher made transcriptions from the data. The results showed that the value of education in Londe Tomatua in the book Londe-Londena Toraya by Pdt.J.B.Lebang which includes religious values, tolerance, hard work, love of peace and responsibility.